Criteria for the importance of multi-scale interactions in turbulent transport simulations. (25th June 2019) - Creely, A J; Rodriguez-Fernandez, P; Conway, G D; Freethy, S J; Howard, N T; White, A E
Abstract: Turbulent transport simulations have been used to develop criteria that indicate when multi-scale turbulent phenomena are important in tokamak plasmas. Twelve experimental plasma discharges from the Alcator C-Mod and ASDEX Upgrade tokamaks are compared to ion- and multi-scale simulations with the Trapped Gyro-Landau Fluid (TGLF) turbulence code. Multi-scale TGLF agrees with all available validation constraints (ion heat flux, electron heat flux, electron temperature fluctuations, and electron perturbative thermal diffusivity) within uncertainty for all cases analyzed. Ion-scale TGLF agrees in only some cases. Two criteria based on the ratios of normalized linear growth rates are able to distinguish cases in which ion-scale simulations are sufficient from cases for which multi-scale simulations are necessary. The form of these criteria reveal the key role of zonal flow mixing in moderating multi-scale effects.